Enabling the Built Environment for Sustainable Living and Climate Resilience - Siew Goh, Cheng; Mokhtar Azizi, Zahirah; Mohd Fateh, Mohd Ashraf; Bajracharya, Arun (European Journal of Sustainable Development, 2024)
Climate crises and a myriad of anthropogenic hazards have induced multitude of diverse impacts on the built environment. These complex and interconnected crises bring impacts on the functionality and integrity of the built environment in various material and immaterial manners, exacerbating the already intense socioeconomic conflicts. Sustainable solutions, if properly planned and implemented, can help build more holistic crises resilience in the built environment by enhancing the capability and capacity to increase preparedness and agility of the built environment to disruptions. This paper aims to provide a better understanding about the research progress on sustainability and resilience of the built environment in response to climate changes. It reviews the impacts of climate crisis on the functionality and integrity of the built environment and examines the importance of integrating resilience in sustainability solution in the built environment. A framework is proposed to unveil how sustainability solutions with an integration of resilience can provide a more solid approach to accelerate the adaptation to and mitigation of climate change impacts within the built environment. Apart from optimising biodiversity and natural resources-based-solutions, sustainable built environment also facilitates powerful partnerships via social transition for environmental governance and human. Sustainability isn’t about decarbonising the built environment. Instead, sustainability would contribute by making systemic changes in the built environment for increased resilience to climate changes and socioeconomic challenges. Keywords: Sustainability, built environment; climate change, resilience, adaptation, systematic review